2019
DOI: 10.3389/fphar.2019.00099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2C19 Metabolizer Status on Escitalopram/Citalopram Tolerability and Response in Youth With Anxiety and Depressive Disorders

Abstract: In pediatric patients, the selective serotonin reuptake inhibitors (SSRIs) escitalopram and citalopram (es/citalopram) are commonly prescribed for anxiety and depressive disorders. However, pharmacogenetic studies examining CYP2C19 metabolizer status and es/citalopram treatment outcomes have largely focused on adults. We report a retrospective study of electronic medical record data from 263 youth < 19 years of age with anxiety and/or depressive disorders prescribed escitalopram or citalopram who underwent rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 55 publications
4
56
1
3
Order By: Relevance
“…20,23,44 The prior meta-analysis that evaluated activation and used a similar definition examined antidepressants in aggregate (ie, SSRIs and SNRIs), thus potentially obscuring SSRI-specific activation. 2 Additionally, SSRI-related activation in pediatric patients is correlated with dose 34 and blood level in several studies; however, the relationship between dose and exposure (eg, blood level) 20 as well as other factors that increase the risk of activation (eg, age) is complex. In the Child/ Adolescent Anxiety Multimodal Study, 1 activation-related AEs were more common in sertraline-treated children compared with adolescents (disinhibition: 5.8% versus 0%; increased motor activity: 4.1% versus 0.8%; restless/fidgety: 2.8% versus 1.6%; significance thresholds for individual events not reported).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,23,44 The prior meta-analysis that evaluated activation and used a similar definition examined antidepressants in aggregate (ie, SSRIs and SNRIs), thus potentially obscuring SSRI-specific activation. 2 Additionally, SSRI-related activation in pediatric patients is correlated with dose 34 and blood level in several studies; however, the relationship between dose and exposure (eg, blood level) 20 as well as other factors that increase the risk of activation (eg, age) is complex. In the Child/ Adolescent Anxiety Multimodal Study, 1 activation-related AEs were more common in sertraline-treated children compared with adolescents (disinhibition: 5.8% versus 0%; increased motor activity: 4.1% versus 0.8%; restless/fidgety: 2.8% versus 1.6%; significance thresholds for individual events not reported).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in children and adolescents treated with escitalopram or citalopram, the number of activation symptoms that patients exhibited (insomnia, irritability, hyperactivity, and impulsivity) was related to the CYP2C19 metabolizer status, with slower metabolizers experiencing more activation symptoms than faster metabolizers (p ¼ .019) in addition to the maximum dose of escitalopram or citalopram (p < .001). 34 Gastrointestinal symptoms have been associated with SSRI/SNRI treatment in pediatric patients 23 but are also influenced by the presence and severity of anxiety disorders. 52 However, in general, gastrointestinal symptoms improve with active treatment, whether psychopharmacologic or psychotherapeutic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is critical that PGx testing be utilized as a guide rather than a replacement for clinical judgment. Further, accumulating data suggest that PGx testing may be utilized to guide dosing, particularly with regard to enhancing tolerability [126]. However, with the exception of FDA guidelines for many psychotropic medications and CPIC guidelines for several additional medications, PGx-driven titration strategies are lacking [127].…”
Section: Cliniciansmentioning
confidence: 99%
“…For example, in sertraline-treated children and adolescents (N = 90), higher plasma concentrations were associated with more antidepressant-related side effects (Taurines et al 2013), and activation is associated with plasma fluvoxamine concentrations in anxious youth (Reinblatt et al 2009). More recently, a retrospective study of escitalopram/citalopram tolerability (N = 248) showed CYP2C19 metabolizer status significantly influenced weight gain, activation, and insomnia (Aldrich et al 2019), suggesting that side effects were related to CYP2C19-related differences in exposure rather than differences in dosing (despite no observed differences in dosing across phenotypes). Taken together, these findings suggest that plasma SSRI concentrations might be related to side effect burden and potentially efficacy.…”
mentioning
confidence: 99%